1967
DOI: 10.5928/kaiyou1942.23.10
|View full text |Cite
|
Sign up to set email alerts
|

Some Observations on the Dependence of Zooplankton Grazing on the Cell Size and Concentration of Phytoplankton Blooms

Abstract: The amount and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(69 citation statements)
references
References 4 publications
2
67
0
Order By: Relevance
“…The energetic benefits of preferential feeding on large prey by fish have been demonstrated theoretically by Kerr (1971) and are supported by laboratory and field evidence. Parsons & LeBrasseur (1970), for example, have shown that juvenile pink salmon (90 mm) were able to satisfy their metabolic requirements when feeding on the relatively large copepod Calanus plumchrus, but that they would undoubtedly starve if they were fed solely on a smaller species Pseudocalanus rninutus, even at much higher concentrations in terms of prey biomass. The benefits of larger prey size have been observed by Kerr & Martin (1970) to counteract the introduction of an intermediate carnivore in a lake ecosystem without affecting the yield of the top carnivore.…”
Section: Generalized Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The energetic benefits of preferential feeding on large prey by fish have been demonstrated theoretically by Kerr (1971) and are supported by laboratory and field evidence. Parsons & LeBrasseur (1970), for example, have shown that juvenile pink salmon (90 mm) were able to satisfy their metabolic requirements when feeding on the relatively large copepod Calanus plumchrus, but that they would undoubtedly starve if they were fed solely on a smaller species Pseudocalanus rninutus, even at much higher concentrations in terms of prey biomass. The benefits of larger prey size have been observed by Kerr & Martin (1970) to counteract the introduction of an intermediate carnivore in a lake ecosystem without affecting the yield of the top carnivore.…”
Section: Generalized Processesmentioning
confidence: 99%
“…The trophic organization of pelagic ecosystems has long been recognized as an important consideration in assessing the ultimate yield of the oceans in terms of fisheries (Steele, 1965;Ryther, 1969;Parsons & LeBrasseur, 1970). Trophic structures of plankton communities in areas of high and low fish yields have been characterized as fundamentally different, based on the position of fish relative to the source of primary production in a linearized food chain.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding experiments with unialgal cultures under laboratory conditions give zero (Frost 1972) or very low values (Frost 1975, Deason 1980, Kiarboe et al 1985a). However, studies in which the copepod were fed a natural assemblage of particulate matter indicate that feeding halts at threshold concentrations significantly greater than zero (Adams & Steele 1966, Parsons et al 1967, Reeve & Walter 1977. A lower feeding thresh-'Addressee for reprint requests old has been included in models of phytoplanktonherbivore interactions (Steele 1974) because it provides the phytoplankton with a refuge in low density so that they cannot be grazed to extinction (Steele & Mullin 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, relating size spectra to conventional measures of primary production is difficult and only a few attempts have been made to consider the biological meaning of the size of particles (Parsons 1969;Sheldon et al 1972;Valkenberg et al 1978;Malone and Chervin 1979 kinds of living and nonliving material (Riley 1970) and each kind will have different nutritional potentials and will vary differently in space and time. A population of grazers will therefore face seasonal and cyclic variations of phytoplankton size fractions and biomass, which will have different residence times in the surface layers (Malone and Chervin 1979).…”
mentioning
confidence: 99%
“…An appreciation of the significance of the size of marine particulate matter has been important in defining in situ feeding characteristics of "herbivorous zooplankton" (Parsons et al 1967;Poulet 1973Poulet , 1974Richman et al 1977;Conover and Huntley 1980;Chervin et al 198 1). Unfortunately, relating size spectra to conventional measures of primary production is difficult and only a few attempts have been made to consider the biological meaning of the size of particles (Parsons 1969;Sheldon et al 1972;Valkenberg et al 1978;Malone and Chervin 1979 kinds of living and nonliving material (Riley 1970) and each kind will have different nutritional potentials and will vary differently in space and time.…”
mentioning
confidence: 99%